Environmental activism? There are apps for that - Aqil, M.I.A. (2020)
For Indonesia, forest conservation and efforts to mitigate and prevent land and forest fires has been a big focus area in the digital space. The severity of annual blazes, which managed to raze 1.65 million hectares of land last year, has pushed environmental groups and government agencies to develop digital tools to help mitigate the disaster.